Мотивація та стимулювання як основні засоби управління персоналом в Україні - Горовий, Д. А.; Строков, Є. М.; Горовой, Д. А.; Строков, Е. М.; Gorovyi, D.; Strokov, Ye. (ЦНТУ, 2019)
В роботі проведено аналіз мотиваційних і стимулюючих заходів на вітчизняному ринку, їх порівняння із закордонними аналогами та розробка дієвого механізму управління персоналом шляхом його мотивації. Обґрунтовано необхідність розробки ефективної системи мотивації праці, здатної на визначення кількісних і якісних індивідуальних результатів праці кожного конкретного працівника та вибір заходів мотивації і стимулювання за кожний конкретний результат. Наведено принципи, на яких повинна базуватися ефективна організація стимулювання і мотивації праці. Запропоновані шляхи створення мотиваційного і стимулюючого ланцюга, що на відміну від існуючих, з одного боку сприяв би мотивації до праці робітника, а з іншого боку – дозволив би організації мінімізувати витрачання коштів, досягаючи у той же час належного рівня мотивації найманого працівника. В работе проведен анализ мотивационных и стимулирующих мер на отечественном рынке, их сравнение с зарубежными аналогами и разработка действенного механизма управления персоналом путем его мотивации. Обоснована необходимость разработки эффективной системы мотивации труда, способной на определение количественных и качественных индивидуальных результатов труда каждого конкретного работника и выбор мер мотивации и стимулирования за каждый конкретный результат. Приведены принципы, на которых должна базироваться эффективная организация стимулирования и мотивации труда. Предложены пути создания мотивационной и стимулирующей цепи, которая, в отличие от существующих, с одной стороны, способствовала бы мотивации к труду работника, а с другой – позволила бы организации минимизировать расходование средств, достигая в то же время должного уровня мотивации наемного работника. The purpose of the article is to analyze motivational and stimulating measures in the domestic market, to compare them with foreign counterparts, and to develop an effective mechanism for managing personnel through their motivation. The methods of general scientific cognition are used, such as analysis, synthesis, induction, comparison. Among the most important elements of personnel management, it is necessary to single out the issue of motivation and stimulation for productive work of personnel. However, under the conditions of inflation (rapid depreciation of money or despondency in their purchasing power), priorities in choosing a source of motivation for both the employer and the worker may change. The analysis of motivational and stimulating measures in the domestic market, their comparison with foreign analogues and the development of an effective mechanism of personnel management through its motivation are carried out in the article. The ways to create a motivational and incentive chain are proposed that, unlike existing ones, would, on the one hand, promote employee motivation and, on the other hand, would allow the organization to minimize spending, while at the same time achieving an adequate level of employee motivation. It should be noted that the employer organization could not completely abandon expensive material stimulation. However, it can minimize it by using only salary payments, and the rest means from other groups. At the same time, at industrial, trading enterprises and service organizations, depending on the position held, the list of motivational funds can vary significantly. The prospect of research on this topic is the development of a motivational algorithm for enterprises and organizations of various fields of activity, the calculation and optimization of the costs of enterprises for carrying out motivational and managerial events.
Мотивация и стимулирования как основные средства управления персоналом в Украине
Motivation and Stimulation as the Main Means of Personnel Management in Ukraine
Keywords: мотивація; стимулювання праці; зарплата; мотив; стимул; оплата праці; продуктивність праці; мотивация; стимулирование труда; зарплата; мотив; стимул; оплата труда; производительность труда; motivation; labor stimulation; salary; motive; stimulus; labor remuneration; labor productivity